Global Pathways: Contrasts and Convergences in Higher Education Internationalization - Amirudin, Jafar; Ijudin; Masripah (Sinergi International Journal of Education, 2025)
The internationalization of higher education has become a critical strategy for enhancing institutional competitiveness, academic mobility, and global engagement. This study aims to compare approaches between developed and developing countries, examining key strategies, systemic barriers, and implications for global education equity. A narrative literature review was conducted using sources from Scopus, Google Scholar, and Web of Science, applying systematic inclusion and exclusion criteria. Keywords such as "internationalization of higher education," "global competitiveness," and "developing countries" guided the search process. The findings reveal that developed countries benefit from comprehensive policy frameworks, robust infrastructure, and institutional autonomy, enabling more effective implementation of internationalization practices. In contrast, developing countries face constraints related to funding, governance, and language proficiency, which hinder their global participation. Notable strategies such as student and faculty mobility, international academic partnerships, curriculum integration, and engagement with the academic diaspora emerged as essential yet unevenly applied. The role of government policy, particularly in facilitating international partnerships and improving language and digital competencies, is pivotal. Despite current efforts, the literature lacks sufficient longitudinal and comparative data, suggesting the need for further research that includes diverse geographic and institutional contexts. This study highlights the urgency for policy-driven, context-sensitive strategies to bridge global disparities and supports inclusive internationalization as a means to achieve balanced global higher education development.